2019
DOI: 10.1111/xen.12565
|View full text |Cite
|
Sign up to set email alerts
|

Decellularized pig pulmonary heart valves—Depletion of nucleic acids measured by proviral PERV pol

Abstract: Background: Decellularized human pulmonary heart valve (dhHV) scaffolds have been shown to be the gold standard especially for younger, adolescent patients.However, human heart valves are limited in availability. Xenogeneic decellularized pig heart valves (dpHV) may serve as alternative. Methods:The efficacy of DNA reduction processes upon decellularization of heart valves from German Landrace pigs was analyzed by measurements of remaining nucleic acids including proviral porcine endogenous retrovirus (PERV) s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…These valves differ significantly from glutaraldehyde‐fixed bioprostheses being vital matrices, open for recellularization, and the resulting physiologic remodeling of the implant 6,26,27 . Even if undergoing a decellularization procedure, the presence of resilient DNA 27‐29 and cells that survive the decellularization procedures were reported 30‐32 . It was shown that none of the present decellularization methods can achieve 100% cell removal, even if the remaining cells are not vital.…”
Section: Classification Of Decellularized Porcine Heart Valves (Dphv)mentioning
confidence: 95%
“…These valves differ significantly from glutaraldehyde‐fixed bioprostheses being vital matrices, open for recellularization, and the resulting physiologic remodeling of the implant 6,26,27 . Even if undergoing a decellularization procedure, the presence of resilient DNA 27‐29 and cells that survive the decellularization procedures were reported 30‐32 . It was shown that none of the present decellularization methods can achieve 100% cell removal, even if the remaining cells are not vital.…”
Section: Classification Of Decellularized Porcine Heart Valves (Dphv)mentioning
confidence: 95%
“…They claimed that the function of decellularized xenogeneic heart valves was comparable to that of allogeneic controls. Godehardt et al also considered that decellularization and nuclease treatment of porcine pulmonary heart valves is an efficient procedure to reduce the DNA content including PERV, which may be beneficial to decrease immunogenicity and zoontic risk 23 . Therefore, efficient decellularization combined with enzymatic removal of DNA might be a feasible method to overcome the immunological barrier causing rapid destruction of the xenogeneic valve.…”
Section: The Advance In Decellularized Pig Pulmonary Heart Valvesmentioning
confidence: 99%
“…However, tissues including heart valves are nowadays decellularized by other means, which asks for a separate consideration in regulatory oversight. Noteworthy, this is increasingly relevant because there is increased interest in using decellularized tissue as scaffold in regenerative medicine and proven evidence of the presence of nucleic acid even after treatment: This was, among others, documented recently in a publication by Antonia Godehardt and coworkers in this journal 15 and resulted in a major point of discussion in the session at the IXA Congress mentioned above. After an opinion paper by Joachim Denner on definitions, the regulation of these decellularized tissues by the European Medicines Agency (EMA) is described by Antonia Godehardt and Ralf Tönjes.…”
mentioning
confidence: 96%